Heat‑related massive chick mortality in an Imperial Cormorant Leucocarbo atriceps colony from Patagonia, Argentina - Quintana, Flavio (2022)
Climate change has exacerbated the frequency and severity of heat waves, which on occasion lead to mass mortalities. Here, we report a massive mortality event in Imperial Cormorant Leucocarbo atriceps chicks that took place during December 2016 at Punta León, one of the two largest colonies (> 6000 pairs) and the northernmost colony for the species in coastal Patagonia, Argentina. During a 2-day period, we estimate that approximately 86.5% of the chicks died. Our results suggest that the mortality event was heat-related, as consequence of an intense heat wave during the brooding period. During two consecutive days, chicks between 12 and 19 days old were exposed to air temperatures above the historical mean of maxima for a total of 25 h. On one of these days, the air temperature reached a maximum of 38.1 °C with records above 35 °C sustained during four consecutive hours. Chicks were found dead throughout the colony, mostly in the nests with no evidence of external injuries other than occasional scavenging by seagulls. Acute mortality from disease was ruled out based on clinical presentation and negative results for avian influenza virus, saxitoxins, and domoic acid (two common marine toxins). Our work underscores the importance of long-term studies in understanding heat associated breeding failure of one of the largest Imperial Cormorant colonies along its breeding range in coastal Patagonia.